Analisis Hukum Eksploitasi Anak Sebagai Pengamen dan Pengemis (Studi Tentang Peran Serta Tanggung Jawab Orang Tua) - Nugraha, Reza Akbar; Prayoga, Ananta Dwi; Amaliya, Maulina; Prama, Yoga Dian; Puspika Sari, Siti Julaeha; Febrianti, Yenny (Indonesian Journal of Law and Justice, 2023)
Children are a gift and responsibility given by God, thus they need to be protected and respected in their basic rights. Child protection is enshrined in the 1945 Constitution and the United Nations child rights convention. Children are the support for the future of the nation and family. Protection for children should commence from within the womb until they reach the age of 18. It is the responsibility of parents, families, and the community to protect the rights of children, while the state and government need to provide facilities and access for the growth and development of children. Child exploitation, such as begging, is a serious problem. The level of poverty is one of the main causes of exploitation. The state and government have an obligation to protect children from exploitation. However, there are still many street children who are vulnerable to exploitation, including physical, economic and sexual exploitation. This research uses a normative legal and empirical juridical approach. In this research, we will explore child protection arrangements in Indonesia, the factors that cause child exploitation, and their impact on children's welfare, with a case study of Decision Number 623/PID.SUS/2016/PN.MLG. With these efforts, we can better understand child protection and the impact of exploitation on child welfare in Indonesia.